2015
DOI: 10.1161/circulationaha.114.013339
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Impaired Endothelial Myocyte Enhancer Factor 2 Function Rescues Pulmonary Arterial Hypertension

Abstract: Background Pulmonary arterial hypertension (PAH) is a progressive disease of the pulmonary arterioles, characterized by increased pulmonary arterial pressure and right ventricular failure. The etiology of PAH is complex, but aberrant proliferation of the pulmonary artery endothelial cells (PAECs) and pulmonary artery smooth muscle cells (PASMCs) is thought to play an important role in its pathogenesis. Understanding the mechanisms of transcriptional gene regulation involved in pulmonary vascular homeostasis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 46 publications
2
112
0
1
Order By: Relevance
“…Finally, correlating with increased PAEC proliferation, our findings revealed a promigratory phenotype promoted by matrix stiffness and the YAP-GLS1 axis ( Figure 6F). A disorder of proliferation and migration has been observed in human plexiform lesions (22), and more recent studies of hyperproliferative PAECs in PH have described an accompanying migratory phenotype (38). Such disordered migration may contribute to abnormal angiogenesis in PH -which in some cases has been linked to a proangiogenic and pathogenic remodeling of the pulmonary arteriole (39) and in other cases has been linked to a deficiency of angiogenesis (39) and a pruning of the entire pulmonary vascular tree.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, correlating with increased PAEC proliferation, our findings revealed a promigratory phenotype promoted by matrix stiffness and the YAP-GLS1 axis ( Figure 6F). A disorder of proliferation and migration has been observed in human plexiform lesions (22), and more recent studies of hyperproliferative PAECs in PH have described an accompanying migratory phenotype (38). Such disordered migration may contribute to abnormal angiogenesis in PH -which in some cases has been linked to a proangiogenic and pathogenic remodeling of the pulmonary arteriole (39) and in other cases has been linked to a deficiency of angiogenesis (39) and a pruning of the entire pulmonary vascular tree.…”
Section: Discussionmentioning
confidence: 99%
“…Selective, pharmacological inhibition of class IIa HDACs using MC1568 restored myocyte enhancer factor 2 activity in IPAH PAECs and rescued from experimental PH (monocrotaline (MCT) and SU5416 plus hypoxia) with no RV fibrosis or coronary artery endothelial cell apoptosis [21]. However, a recent study reported that the class IIa HDAC inhibitor MC1568 moderately suppressed class IIb HDACs, but failed to inhibit class IIa HDAC catalytic activity on a class-selective synthetic substrate in rat left ventricular homogenates [23], while other studies report pan-inhibition of both class IIa and class IIb HDAC isoforms by MC1568 employing recombinant proteins on histones [24].…”
Section: Deregulation Of Hdac Isoforms and Therapeutic Evaluationmentioning
confidence: 98%
“…However, only three studies have reported evidence of aberrant gene or protein expression of HDAC isoforms in pulmonary tissues, including human lung homogenates (HDAC1, HDAC4 and HDAC5) [20], human PAH-PAECs (HDAC4 and HDAC5) [21] and from pulmonary adventitial fibroblasts from chronically hypoxic calves (HDAC1, HDAC2 and HDAC3) [9]. However, the pulmonary vascular cell-specific expression and molecular function of specific HDAC isoforms in health and disease remains to be thoroughly explored in PH.…”
Section: Deregulation Of Hdac Isoforms and Therapeutic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The impaired MEF2 activity in ECs from PAH was associated with increased nuclear accumulation of HDAC4 and HDAC5. So, increasing MEF2 activity by the selective inhibition of class IIa HDACs by MC1568 seems to suppress excessive EC migration and proliferation by PAH-ECs and can rescue experimental PAH model [106]. Although the increased migration and proliferation of pulmonary artery ECs in PAH are also hallmarks of angiogenesis, it is still contentious to link excessive angiogenesis with the pathogenesis of PAH [107], and any potential anti-angiogenic therapy for PAH should be proceeded with caution.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%